A review of maternal and fetal outcome of induction of labour with Foley’s catheter and extra amniotic saline infusion in women with previous caesarean delivery - Kumar, Sunil; Mahabalshetti, Nishtha A.; Dinu Simon, Dinu Simon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Incidence of induction of labour has increased in the recent past due to increased screening facilities like ante partum fetal surveillance. Vaginal birth after caesarean section (VBAC) is one of the strategies developed to control the rising rate of caesarean sections. Intracervical Foley’s catheter reduces the risk of uterus hyper tonicity and rupture in women with one caesarean section as it’s placement induces the cervical repining without inducing any uterine contractions. Methods: A prospective study of 35 women with one previous LCSs, term gestation and singleton pregnancy, were selected for trial of labour (TOL) considering inclusion and exclusion criteria. Results: Out of 35 cases studied 21 cases (60%) went for successful induction with Foleys and the remaining 40% underwent caesarean section. The mean time interval for Foley’s expulsion was 6.74 in the success group and 10.04 in the failed group (p value <0.05). In 4 cases there were meconium stained liquor, and they underwent emergency LSCS. One case (2.8%) had scar rupture which also underwent caesarean section. Conclusions: This study shows that the Foley catheter is an effective method of cervical ripening with additional benefit of low cost, reversibility, easy availability and lack of need for special storage. This method confers significant improvement in Bishop Score and vaginal delivery was achieved in majority of patients.